Penyuluhan Alat Kontrasepsi pada Ibu Pasangan Usia Subur di Posyandu Melati III - Sanjaya, Riona; Kusumawardani, Amalia; Yanti, Dwi; Fatimah, Fita; Andrian, Gusri (Pencerah, 2023)
Family planning is a way that allows people to achieve the number of children they want and determine the spacing of pregnancies, where this can be achieved through the use of contraceptive methods and infertility treatment (World Health The maternal health services provided include health services for pregnant women, health services for postpartum women, health centers conducting classes for pregnant women and the Birth Planning and Complications Prevention Program (P4K), and contraception/KB services. In general, the aim of implementing the family planning program is to increase the capacity of MCH/IMR program managers in terms of management of family planning services as an effort to support the accelerated reduction of maternal and infant mortality rates.The purpose of this community service activity is to synthesize creative ideas through an educational program with an emphasis on preventive and promotive efforts in preventing and overcoming population growth. The implementation of this community service activity was attended by mothers of couples of childbearing age, totaling 18 participants at the posyandu. The method used in this activity is through lectures, and discussion and question and answer, where before and after the activity is given a pretest and posttest. This activity increases the understanding of mothers of couples of childbearing age about family planning, especially the types of tools.